2020
DOI: 10.1186/s12887-020-02297-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the scale-up and implementation of mind, exercise, nutrition … do it! (MEND) in British Columbia: a hybrid trial type 3 evaluation

Abstract: Background: The Mind, Exercise, Nutrition … Do it! (MEND) childhood obesity intervention was implemented in British Columbia (B.C.), Canada from April 2013 to June 2017. The study objective was: a) to describe and explore program reach, attendance, satisfaction, acceptability, fidelity, and facilitators and challenges during scale-up and implementation of MEND in B.C. while b) monitoring program effectiveness in improving children's body mass index (BMI) z-score, waist circumference, dietary and physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For example, a previous 12-week family-based childhood obesity management intervention (children aged 8-12 years) showed that MVPA increased by 53 minutes per week and screen time decreased by 34 minutes per day [31]. Similarly, in a previous 10-week family-based intervention (MEND) delivered in British Columbia, children showed an increase in weekly physical activity levels by 2.6 hours per week and a decrease in screen time by 3 hours per week following the intervention [10].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, a previous 12-week family-based childhood obesity management intervention (children aged 8-12 years) showed that MVPA increased by 53 minutes per week and screen time decreased by 34 minutes per day [31]. Similarly, in a previous 10-week family-based intervention (MEND) delivered in British Columbia, children showed an increase in weekly physical activity levels by 2.6 hours per week and a decrease in screen time by 3 hours per week following the intervention [10].…”
Section: Discussionmentioning
confidence: 90%
“…This may have been due to the lockdown, as parents may have more opportunities to influence children's vegetable intake while they are at home every day [25]. However, previous childhood obesity interventions delivered in-person have reported significant improvements in dietary behaviors [10,11,35,36]. The lack of significant changes in the intake of fruits and sugary drinks may reflect a ceiling effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included articles were recent in publication, ranging from 2010 to 2021. The 27 articles in this review consisted of 12 case studies [ 21 , 36 46 ], 4 study protocol papers [ 47 50 ], 3 randomized control trials [ 51 53 ], 2 quasi-experimental trials [ 54 , 55 ], 2 longitudinal studies [ 56 , 57 ], 1 prospective evaluation [ 58 ], 1 cross-sectional study [ 59 ], 1 review [ 60 ], and 1 systematic review [ 61 ]. A majority of the articles used mixed methods (e.g., surveys, interviews, workshops, community reports) to report on the implementation of their programs ( n = 13) [ 21 , 38 43 , 47 , 51 , 52 , 57 , 58 , 60 ], while the remained focused on quantitative ( n = 10) [ 43 , 45 , 48 50 , 53 55 , 59 , 61 ] or qualitative measures ( n = 4) [ 36 , 42 , 44 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the requirements of in-person interventions such as travel to a location or missing work responsibilities, their structures are often limited in flexibility and scalability [ 14 ]. Emerging evidence has indicated the inclusion of digital technologies (eg, smartphones, tablets, computers, and wearables) in conjunction with in-person, family-based interventions, which may allow researchers to increase both program outreach and provide flexibility for families [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%